Effects of some factors on perinatal mortality: Analysis by the method of multiple regression binary - Gonzales Enders, Rodolfo (2015)
The effects of seven independent variables on the dependent variable Perinatal Mortality is analyzed, using the data obtained retrospectively prospective, consecutive thousand births occurring between February and June 1973 at the General Hospital Cayetano Heredia Base. The number of intrapartum complications and type of presentation are the only independent variables with statistical significance. It should also be considered that the effect of the interrelationship of variables is a significant fact, both for handling the individual patients, as the population groups.